Pengaruh Gaya Hidup dan Teman Sebaya Terhadap Perilaku Keuangan Pembelian Sepeda Pandemi Covid-19 Bojong Kulur-Bogor - Naufal Wahyu Ramadhan; Mawarta Onida Sinaga; Fortuna Zain Hamid (Administratif Profesional, 2022)
This study aims to determine and analyze whether there is a partial and simultaneous influence between Lifestyle and Reference Groups (Peers) on Financial Behaviour on the Phenomenon of Buying Bikes during the Covid-19 Pandemic in Bojong Kulur Village - Bogor Regency. The research used in this study is causal associative research with a quantitative approach. The data analysis method uses instrument test analysis, classical assumption test, and hypothesis testing. The sample selection method used purposive sampling. The samples obtained using the Slovin formula are as many as 100 respondents. The results of this study indicate that: This study meets the normal distribution requirements, namely 0.200 > 0.05. The regression equation model Y = 5.956 + 0.606 (x1) + 0.200 (x2) + shows the research is feasible to use. Based on the results of partial correlation, lifestyle variables have an influence on financial behaviour by 41.21 percent, while the reference group variable (peers) has an influence on financial behavior by 29.26 percent. The financial behavior variable is influenced by lifestyle variables and reference groups (peers) by 47.1 percent, while 52.9 percent is influenced by other variables that are not used in this study